2020
DOI: 10.1002/nau.24303
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of the proportion of uncertain diagnoses of pudendal neuralgia in women with chronic pelvic‐perineal pain: A systematic review with a descriptive data synthesis

Abstract: Background There is a gap between pudendal neuralgia (PN) due to pudendal entrapment syndrome and PN without pudendal entrapment syndrome. The latter could have atypical symptoms. Aim Defining a rate of atypical PN from a clinical series of female patients with chronic pelvic‐perineal pain. Methods The atypical PN was defined as a pain not meeting clinical criteria for pudendal entrapment syndrome. The effect size was the rate of atypical PN. Such a rate was expected to be found among patients screened for enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…Until now only the Nantes criteria are considered as a golden standard in helping to diagnose this rare condition. 4,11,12 When diagnosis is suspected, treatment should be offered in a multidisciplinary setting to optimize treatment outcome. Behavioral therapy, physiotherapy, neuropathic pain drugs, pudendal and/or cluneal nerve infiltrations are such treatment options, but long term efficacy is disappointing for some.…”
Section: Discussionmentioning
confidence: 99%
“…Until now only the Nantes criteria are considered as a golden standard in helping to diagnose this rare condition. 4,11,12 When diagnosis is suspected, treatment should be offered in a multidisciplinary setting to optimize treatment outcome. Behavioral therapy, physiotherapy, neuropathic pain drugs, pudendal and/or cluneal nerve infiltrations are such treatment options, but long term efficacy is disappointing for some.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of a recently published systematic review concluded that Nantes' criteria are the gold standard for diagnosing typical PN as well as PNE syndrome. 11 If 1 or more of the clinical essential Nantes' criteria are not met then atypical PN can be presumed, though this is thought to be low at ∼1% of patients. 11 There are 5 essential diagnostic criteria Often patients will report they do not tolerate tight clothing and can sit on the toilet seat without pain, but not on flat surfaces.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…11 If 1 or more of the clinical essential Nantes' criteria are not met then atypical PN can be presumed, though this is thought to be low at ∼1% of patients. 11 There are 5 essential diagnostic criteria Often patients will report they do not tolerate tight clothing and can sit on the toilet seat without pain, but not on flat surfaces. Patients may also favor one side of their pelvis while sitting.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
See 1 more Smart Citation